Analysis of Human Factor Risks in Offshore Platforms Using Human Factors-Failure Mode and Effect Analysis (HF-FMEA) - Sevah, Sukhania; Ghazilla, Raja Ariffin Raja; Yap, Hwa Jen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Many occupational accidents that beset the oil and gas industry globally have been attributed to human errors and other operational constraints. Accident analyses revealed that offshore facilities have a diversified set of equipment focusing on the process requirement rather than system design. This paper aims to create a framework to assess the human factors, hazards or risks associated with maintenance activities within an offshore facility. In pursuit of this goal, a methodology was employed that integrated Failure Mode and Effect Analysis (FMEA) with Human Factors (HF) criteria, resulting in the development of a comprehensive accident analysis framework known as HF-FMEA. This approach considers potential failure modes and also incorporates human factors considerations, thereby enhancing the overall robustness of the analysis. The HF-FMEA framework not only identifies and evaluates failure modes and their potential effects but also takes into account human elements, providing a more holistic understanding of the factors contributing to accidents.